2021
DOI: 10.1021/acscatal.0c03511
|View full text |Cite
|
Sign up to set email alerts
|

Transition-Metal- and Nitrogen-Doped Carbide-Derived Carbon/Carbon Nanotube Composites as Cathode Catalysts for Anion-Exchange Membrane Fuel Cells

Abstract: Transition-metal- and nitrogen-codoped carbide-derived carbon/carbon nanotube composites (M-N-CDC/CNT) have been prepared, characterized, and used as cathode catalysts in anion-exchange membrane fuel cells (AEMFCs). As transition metals, cobalt, iron, and a combination of both have been investigated. Metal and nitrogen are doped through a simple high-temperature pyrolysis technique with 1,10-phenanthroline as the N precursor. The physicochemical characterization shows the success of metal and nitrogen doping a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(65 citation statements)
references
References 90 publications
(149 reference statements)
1
64
0
Order By: Relevance
“…M-N-C-type catalysts are promising candidates due to their high ORR electrocatalytic activity, resistance toward corrosion, and high active surface area. 25 , 58 , 59 …”
Section: Introductionmentioning
confidence: 99%
“…M-N-C-type catalysts are promising candidates due to their high ORR electrocatalytic activity, resistance toward corrosion, and high active surface area. 25 , 58 , 59 …”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37][38][39][40][41][42] Thus, one approach to prepare MÀ NÀ C catalysts that contain these specific catalytic active sites is by high-temperature pyrolysis in the presence of transition metal salts (e. g. iron or cobalt acetate) and nitrogen precursor (e. g. 1,10-phenanthroline) along with carbon support materials in inert atmosphere. [16,43,44] Another interesting way to form M-N x centres and metal oxides in carbon matrix is to use MN 4 macrocyclic compounds (e. g. transition metal phthalocyanines or porphyrins) for this purpose. Such as, MÀ NÀ C type catalysts derived from different metal phthalocyanines (MPcs) in the combination of various carbon supports have been prepared and studied towards the ORR, OER and for both, the ORR and OER processes.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been observed that incorporation of M‐N x centres and MO x onto conductive carbon support provide remarkable ORR and OER electrocatalysis, respectively [35–42] . Thus, one approach to prepare M−N−C catalysts that contain these specific catalytic active sites is by high‐temperature pyrolysis in the presence of transition metal salts (e. g. iron or cobalt acetate) and nitrogen precursor (e. g. 1,10‐phenanthroline) along with carbon support materials in inert atmosphere [16,43,44] . Another interesting way to form M‐N x centres and metal oxides in carbon matrix is to use MN 4 macrocyclic compounds (e. g. transition metal phthalocyanines or porphyrins) for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…silver, nickel), and nitrogen co-doped carbons have been investigated and used as the ORR catalysts. [16][17][18][19][20][21][22][23][24] Transition metal oxides (TMOs) of spinel structure are commonly applied as catalysts for the ORR in AEMFCs. Numerous TMOs exhibit satisfactory catalytic activity in the ORR and the oxygen evolution reaction (OER) with the advantages of being inexpensive, naturally abundant, and environmentally benign.…”
Section: Introductionmentioning
confidence: 99%